Participation of Civil DE fence Volunteers in Disaster Prevention and Mitigation Operations, Chachoengsao Municipality, Mueang Chachoengsao District, Chachoengsao Province - โพธิ์เกษม, ภนิดา; รชตวัฒนกุล , สุวัจ; รชตวัฒนกุล, สนใจ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
This research aimed to 1) study the participation of civil defense volunteers in disaster prevention and relief work in Chachoengsao Municipality, Mueang Chachoengsao District, Chachoengsao Province. 2) compare the participation of civil defense volunteers in disaster prevention and relief work in Chachoengsao Municipality, Mueang Chachoengsao District, Chachoengsao Province, classified by personal factors. 3) to propose guidelines for developing the participation of civil defense volunteers in disaster prevention and relief work in Chachoengsao Municipality, Mueang Chachoengsao District, Chachoengsao Province. The research method used a qualitative mixed-methods approach. The key informants were 187 people. Data were collected using unstructured interviews. Data were analyzed using descriptive techniques. Quantitative research, a sample of 187 people, was obtained using the ready-made table of Krejci and Morgan. Data were collected using a questionnaire. Data were analyzed by finding percentages, means, and standard deviations.